2021
DOI: 10.52462/jlls.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of language learning strategies and stereotypical thoughts of preparatory school students

Abstract: This study identifies the usage of language learning strategies and stereotypical thoughts on foreign languages regarding gender and language marks. It is designed in both correlation model and descriptive comparative model. The research sample is composed of 184 preparatory school students studying at a state university. Two questionnaires are used in the collection of data: Oxford's Language Learning Strategies Scale (1990) and Ünal's (2015) Stereotypical Thoughts towards Foreign Language Scale. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
“…Canbay [23] described the relationship between self-regulation and LLS of 264 secondary school students. Irgatoğlu [21] analyzed the usage of LLS and stereotypical thoughts of 184 preparatory school students, regarding gender and language marks. Other studies that assessed learners' selection of LLS at the school level are Duong and Nguyen's [52] studies could be regarded as continuing the tradition of LLS research since they relied on the SILL to identify students' use of strategies and explored the relationships with other variables.…”
Section: Educational Settings In Lls In Efl Contextsmentioning
confidence: 99%
“…According to Yalcin (2005), Wenden and Rubin defined learning strategies as "any set of operations, steps, plans, routines used by the learner to facilitate the acquisition, storage, retrieval, and utilization of information." Yalcin (2005) distinguished between two types of learning processes: direct and indirect strategies.…”
Section: Grammar Learning Strategiesmentioning
confidence: 99%
“…Furthermore, Yalcin (2005) discovered that 70.2% of Preparatory School students at the University of Gaziantep employ grammar learning styles that include cognitive, metacognitive, and social/affective. Cognitive learning allows pupils to improve their understanding, acquisition, and retention.…”
Section: Grammar Learning Strategiesmentioning
confidence: 99%
See 1 more Smart Citation